Effect of think-pair-share strategy on student achievement in senior secondary school mathematics - Abiodun, Taiwo Oluwadayo; Asanre, Akorede Ayoola; Ogundeji, Moses Adegbola; Odupe , Toyin A; Rasaki, Musa Gbolahan (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2022)
This study examined the effect of the Think-Pair-Share strategy on student achievement in secondary school Mathematics in Ogun State Nigeria. The study adopted a pretest, posttest, and control group quasi-experimental design using 2x2 factorial matrix. The population of the study was made up of all twenty-two thousand and seventy (22,070) Senior Secondary Schools 2 (SSS2) students in Ogun State, Nigeria. Three hypotheses guided the study. Purposive Sampling Technique was used to select four (4) Senior Secondary Schools in Ijebu-Ode and Ijebu-North East Local Government Areas respectively. Twenty students were selected from each of the schools by using the Simple Random Sampling Technique. Eighty students participated in the study which was made up of forty (40) males and forty (40) females respectively. The instrument used for data collection is titled Mathematics Achievement Test (MAT) with a Reliability Coefficient of 0.78 by using Pearson Correlation. The collected data were analysed using descriptive statistics (Mean and Standard Deviation) and inferential statistics (Analysis of Covariate was used to analyze the stated hypotheses at a 0.05 level of significance. Findings revealed that there is the main effect of the strategy on the student’s achievement in Mathematics. Also, it was established that there is no significant main effect of gender on the achievement of the students in Mathematics. Therefore, the researcher recommends among others that, the Think-Pair-Share method of teaching should be incorporated into the learning and teaching of Mathematics in Senior Secondary Schools.